CU06-1004 Alleviates Experimental Colitis by Modulating Colonic Vessel Dysfunction - Kim, Ye-Seul; Zhang, Haiying; Lee, Sunghye; Park, Songyi; Noh, Minyoung; Kim, Young-Myeong; Kwon, Young-Guen (Frontiers in Pharmacology, 2020)
Inflammatory bowel disease is an autoimmune disease that causes chronic inflammation of the gastrointestinal tract. Endothelial dysfunction, defined by a reduced endothelial barrier and an increase in the expression of adhesion molecules, is part of the pathology of inflammatory bowel disease. In this study, we assessed the therapeutic effect of CU06-1004, an endothelial dysfunction blocker that reduces vascular hyperpermeability and inflammation in a mouse model of colitis. Acute colitis was induced in mice using 3% (w/v) dextran sodium sulfate added to their drinking water for seven days. Twenty-four hours after the addition of dextran sodium sulfate, either mesalazine or CU06-1004 was administered orally each day. Administration of CU06-1004 significantly reduced the clinical manifestations (weight loss, diarrhea, and bloody stool) and histological changes (epithelium loss, inflammatory cell infiltration, and crypt destruction) induced by dextran sodium sulfate. Pro-inflammatory cytokines were also reduced, indicating that inflammation was ameliorated. From a vascular perspective, CU06-1004 reduced interrupted and tortuous vessels, enhanced junction protein expression, and reduced inflammatory adhesion molecules, indicating a broad improvement of endothelial dysfunction. Endothelial protection induced epithelial barrier restoration and decreased epithelial inflammation. Blocking endothelial dysfunction with CU06-1004 significantly ameliorated the progression of inflammatory bowel disease. Therefore, CU06-1004 may represent a potential therapeutic agent for the treatment of inflammatory bowel disease as well as other inflammatory diseases.